The microbiota regulates murine inflammatory responses to toxin-induced CNS demyelination but has minimal impact on remyelination - McMurran, Christopher E. (Proc Natl Acad Sci U S A, 2019)
The microbiota is now recognized as a key influence on the host immune response in the central nervous system (CNS). As such, there has been some progress toward therapies that modulate the microbiota with the aim of limiting immune-mediated demyelination, as occurs in multiple sclerosis. However, remyelination—the regeneration of myelin sheaths—also depends upon an immune response, and the effects that such interventions might have on remyelination have not yet been explored. Here, we show that the inflammatory response during CNS remyelination in mice is modulated by antibiotic or probiotic treatment, as well as in germ-free mice. We also explore the effect of these changes on oligodendrocyte progenitor cell differentiation, which is inhibited by antibiotics but unaffected by our other interventions. These results reveal that high combined doses of oral antibiotics impair oligodendrocyte progenitor cell responses during remyelination and further our understanding of how mammalian regeneration relates to the microbiota.